Reduction of Heavy Metal Ions Cu2+ and Pb2+ in Electroplating Wastewater Using an Ion Exchange Column - Nurul Safira Maulida Agustina (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Electroplating wastewater are hazardous because it contains heavy metals, such as copper and lead, at concentrations exceeding environmental standards. This study aimed to evaluate the effects of resin height and flow rate on the removal of Cu2+ and Pb2+ using an ion-exchange column packed with Dowex Amberlite IRC120 Na resin. The wastewater sample had an initial Cu concentration of 37,8 mg/L and Pb concentration of 3,33% mg/L, both above the applicable quality standard. The process was carried out using resin heights of 20, 25, 35, 45, and 55 cm and flow rates of 30, 55, 65, 75, and 80 mL/min with three recirculation cycles. The results showed that increasing resin height tended to improve metal removal, while lower flow rates provided longer contact time and better exchange performance. The best result was obtained at a resin height of 20 cm and a flow rate of 80 mL/min, with final concentrations of 0.014 mg/L for Cu²⁺ and 0.013 mg/L for Pb²⁺. These results indicate that ion exchange is effective for reducing heavy metals in electroplating wastewater and meets the required discharge standard.